2016
DOI: 10.1177/0308022615627174
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of academic performance and education programme satisfaction in occupational therapy students

Abstract: Introduction: Thriving and performing well in entry-level programmes is important to occupational therapy students, but also for the competitive status of the institutions providing their education. The literature is sparse concerning the factors of importance for occupational therapy students' academic performance in, and satisfaction with, their education programme. Method: This cross-sectional study explored sociodemographic-, relationship-, education-, and work-related variables and their associations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 20 publications
1
30
0
2
Order By: Relevance
“…In line with the above, previous studies have found more higher education experience to be associated with better academic performance among occupational therapy students (Bonsaksen, 2016;Shanahan, 2004). Given the preference for challenge and personal growth found in more mature students (Seah, Mackenzie, & Gamble, 2011), it is possible that the association between experience and better academic performance is mediated by more productive study approaches by the more experienced students.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…In line with the above, previous studies have found more higher education experience to be associated with better academic performance among occupational therapy students (Bonsaksen, 2016;Shanahan, 2004). Given the preference for challenge and personal growth found in more mature students (Seah, Mackenzie, & Gamble, 2011), it is possible that the association between experience and better academic performance is mediated by more productive study approaches by the more experienced students.…”
supporting
confidence: 75%
“…Having more study experience has been found to be associated with better academic performance among occupational therapy students (Bonsaksen, 2016;Shanahan, 2004), possibly mediated by more productive study approaches being applied by the more experienced students. Third-year students, having already completed two-thirds of their occupational therapy education, including the larger part of their clinical practice training, have presumably acquired more serviceable study skills and a better understanding of their discipline.…”
Section: Discussionmentioning
confidence: 99%
“…Being older naturally increases the possibility of having prior higher education, and the latter was also directly associated with higher deep approach scores. Both age and academic experience may add to the students maturity, as suggested from prior research -students who had previous experience from higher education had higher average exam grades, compared to their counterparts without similar experience [43].…”
Section: Sociodemographic Covariates To Study Approachesmentioning
confidence: 88%
“…Abrimos espaços para reflexões sobre as demandas da sociedade, das instituições, dos projetos, mas, principalmente, a demanda e o desejo dos sujeitos, que podem ser diferentes das necessidades identificadas a partir do saber técnico narrativo-científico 12,13 . Essas reflexões fomentam questionamentos sobre ações em terapia ocupacional que vislumbrem a construção de uma história compartilhada, na qual ambos possam investir 14 .…”
Section: Discussionunclassified
“…Nesse processo, ao explorar racionalidades e emoções 8 , os estudantes experimentam pensamentos e sentimentos reais como terapeutas ocupacionais e poder falar sobre essas vivências é avaliado como algo realmente importante. Ter um momento garantido na estrutura curricular para a reflexão do seu próprio "estudo" parece gerar maior satisfação entre os estudantes, na medida em que eles se percebem como pessoas com sentimentos, conceitos e valores que devem ser revisitados e, algumas vezes, transformados para o exercício da prática profissional 12 .…”
Section: Discussionunclassified